2001
DOI: 10.3136/fstr.7.126
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Distribution of Protein Hydrolysate by the Enzymic Hydrolysis of Weakly Acid-Treated Wheat Gluten

Abstract: For the production of highly soluble HVP (hydrolysed vegetable protein) by enzymic hydrolysis, wheat gluten suspension (6% w/w, protein) was pretreated with weak acid (0.1 N HCl) at 95°C for 1 h to overcome insolubility of the suspension. After treating it for 3 h with alcalase, flavourzyme was added to the wheat gluten hydrolysate and hydrolysis continued for a further 21 h at 50°C. ␣-Amino nitrogen content (AN, mg/ml) and nitrogen solubility index (NSI, %) of the resulting wheat gluten hydrolysate product wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…the percentage of peptide bonds cleaved), the higher the proportion of low molecular weight fractions in the final product. 49 However, our results indicate that choosing a particular peptone by taking into consideration only the degree of hydrolysis (DH) can result in unpredictable effects on cell proliferation. We hypothesise that, for peptones with the same DH, the combination of enzymatic cocktail and raw material used in the manufacturing process can also considerably influence the performance of the resulting peptone.…”
Section: Discussionmentioning
confidence: 84%
“…the percentage of peptide bonds cleaved), the higher the proportion of low molecular weight fractions in the final product. 49 However, our results indicate that choosing a particular peptone by taking into consideration only the degree of hydrolysis (DH) can result in unpredictable effects on cell proliferation. We hypothesise that, for peptones with the same DH, the combination of enzymatic cocktail and raw material used in the manufacturing process can also considerably influence the performance of the resulting peptone.…”
Section: Discussionmentioning
confidence: 84%
“…5D)]. Hong et al [28] reported the similar MW distribution pattern after 24 h hydrolysis of WG with Alcalase and Flavourzyme. However, after SCW treatment at 220°C, MW of almost of them decreased to less than 6500 Da.…”
Section: Changes In Molecular Weight Distributionmentioning
confidence: 86%
“…Acid hydrolysis often provides some problem such as undesirable tastes, odors, and loss of essential amino acids, but it can be easily applied in commercial conditions due to the economic advantages and without worrying about microbial contamination during long reaction time (Lahl and Braun, 1994). Hong et al (2001) reported that acid pretreatment (0.1 M HGl at 95°G for 1 h) accelerated the subsequent enzymatic hydrolysis process by activating enzymes or enhancing the solubility of proteins.…”
Section: Inhibitory Effects On H2o2-lnduced Dna Damagementioning
confidence: 99%